Communities of ground‐dwelling arthropods in conventional and transgenic maize: background data for the post‐market environmental monitoring. (7th August 2014) - Skoková Habuštová, O.; Svobodová, Z.; Spitzer, L.; Doležal, P.; Hussein, H. M.; Sehnal, F.
Abstract To verify the validity of concerns about environmental safety of maize expressing insecticidal Cry toxins (referred to as Bt maize), we compared communities of ground beetles (Carabidae), rove beetles (Staphylinidae) and spiders (Araneae) in plots planted either with Bt maize cultivar YieldGard® or with the non‐transgenic parental cultivar Monumental. Each cultivar was grown on 5 plots of 0.5 ha for three consecutive years. To increase the field load of Cry toxin, the fully grown maize of the first study year was shredded to small pieces that were ploughed into the soil. Arthropods were collected in pitfall traps and determined to the species level. The abundance and species richness of all studied groups greatly varied over the season and between the seasons but without statistically significant differences between the Bt and non‐Bt plots. A single spider species and three ground beetle species dominated in the catches every year, whereas a set of 1–4 most abundant rove beetle species changed every year. Frequently occurring species were typical for most of Europe. The total counts of ground beetles, rove beetles and spiders collected once or twice per season are proposed to serve as bioindicators in the post‐market environmental monitoring (PMEM).